Penentuan Nilai SPF, Persentase Eritema dan Persentase Pigmentasi Ekstrak Metanol dan Fraksi N-Heksan, Etil Asetat, dan Butanol Daun Melinjo (Gnetum Gnemon L.) Secara In-Vitro - Bagus Nurprialdi; Purwati (PT. Hasba Edukasi Mandiri, 2025)
This research examines the potential of melinjo leaves (Gnetum gnemon L.) as a natural sunscreen, with a focus on the content of phenolic compounds, especially flavonoids. Through plant determination, sample preparation, methanol extraction (12.416% yield) and multilevel fractionation (n-hexane 12.1%, ethyl acetate 11.86%, butanol 10.16%), as well as examination of extract and fraction characteristics, phytochemical screening showed the presence of tannins, alkaloids, flavonoids, saponins (except the butanol fraction), steroids (methanol extract and n-hexane fraction), and terpenoids (ethyl acetate and butanol fractions). Melinjo leaf extract meets the Indonesian Herbal Pharmacopoeia standard for ash content (6%) and is safe from heavy metal contamination (Hg, Pb, Cd), with a water content of 2.98% and a pH of between 4.5-6.5. The in-vitro sunscreen activity test showed high SPF values ​​(High category) in the methanol extract and fractions (especially 1000 ppm), with the lowest %Te (Sunblock category) in the methanol extract and n-hexane fraction (200 and 250 ppm). Ethyl acetate and butanol fractions (1000 ppm) are effective in preventing skin pigmentation (Sunblock category). It was concluded that melinjo leaves have potential as a natural sunscreen because of their flavonoid content, with extracts and fractions showing good sunscreen activity, but only the highest concentrations of ethyl acetate and butanol fractions are effective in preventing pigmentation.